PENGARUH PIJAT OKSITOSIN TERHADAP PENINGKATAN PRODUKSI ASI IBU MENYUSUI : A SYSTEMATIC LITERATURE REVIEW - Angela Lovendra Naingalis (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2023)
ASI (Breast Milk) is milk produced by the mother and contains all the nutrients needed by the baby for the growth and development needs of the baby. Efforts to overcome problems that cannot be done in postpartum mothers other than breast care is with oxytocin massage. Journal searches were carried out electronically using several databases, namely: Garuda Portal and Google Scholar from 2013-2022. The keywords are breastfeeding mother, breastmilk production, oxytocin massage. The research results of selected articles from 5 national journals concluded that oxytocin massage can increase milk production in post partum mothers.Keywords: Post Partum, Oxytocin Massage, Breast Milk Production